Expired Colxacillin, Amoxicillin, and Ceflaxin Drugs as Inhibitors for Low Carbon Steel Corrosion in Sodium Chloride - Jawad, Ameer; K. Muallah, Shatha; Hammud, Kafa Khalaf (Al-Khwarizmi Engineering Journal, 2023)
The ability to inhibit corrosion of low carbon steel in a salt solution (3.5%NaCl) has been checked with three real expired drugs (Cloxacillin, Amoxicillin, Ceflaxin) with variable concentrations (0, 250, 500, 750) mg/L were examined in the weight loss. The inhibition efficiency of the Cloxacillin 750 mg/L showed the highest value (82.8125 %) and the best inhibitor of the rest of the antibiotics. The different concentrations of Cloxacillin drug (0, 250, 500, 750) mg/L and temperature (25, 35, 45, 55) oC were studied as variables with potentiodynamic polarization, Scanning Electron Microscopy (SEM) for surface morphology and electrochemical impedance spectroscopy (EIS) depending on current values and the resistance of charge to calculate the inhibition efficiency. The main observations of these tests were that polarization curves showed a mixed-type inhibition of expired Cloxacillin. The inhibition efficiency increased with increasing Cloxacillin concentration but not with increasing temperature.